Land Redistribution of Accretion Land within Indonesia’s Agrarian Reform Framework - Adellya Salsabilla Hermawan; Suhadi Suhadi (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the juridical status of accretion land within Indonesia’s land law system and to examine its operational integration into the agrarian reform framework through the Agrarian Reform Object Land (TORA) mechanism. Employing a normative juridical approach, this research is based on statutory and conceptual analysis using deductive legal reasoning to assess the coherence between legal norms and their practical application. The findings reveal that although accretion land is formally classified as state-controlled land, its governance is characterized by a significant gap between normative regulation and empirical utilization by coastal communities, resulting in legal uncertainty, administrative ambiguity, and potential agrarian conflicts. Furthermore, accretion land demonstrates substantial strategic value as a redistribution object within agrarian reform, particularly in strengthening tenure security and promoting socio-economic welfare; however, its implementation remains constrained by fragmented regulations, overlapping authority, and limited institutional capacity. The novelty of this study lies in the explicit conceptualization of accretion land as a systematic and legally viable component of agrarian reform, accompanied by the development of an integrative legal-operational framework that bridges doctrinal law with empirical land use practices in coastal areas. This study contributes both theoretically, by advancing agrarian law discourse through the integration of normative and practical perspectives, and practically, by offering policy-oriented recommendations to enhance regulatory harmonization, institutional coordination, and equitable land governance.